Insurance: An Introductory Text - Falegan, J. I. (Lagos: University of Lagos Press, 1991)
This book gives comprehensive coverage of the introductory courses of the Insurance Institute of Nigeria and the institutions of higher learning offering insurance course in their curriculum. It is written in a simple language for easy comprehension not only by professional students of insurance but also those students taking other professional examinations in which the knowledge of insurance is a prerequisite.
Includes index.
Includes bibliographical references: p. 162-167.
ne 10/05/2018
Loan
Keywords: Insurance; NIgeria